Service Sector and Privatization of Services (International Journal of Food and Nutritional Sciences, 2022)
Education, Health, Transport, Electricity, Banks in India's service sector. Insurance Plans, TelecomServices, Railway Services. Financial services, public enterprises and administrative services are beingcovered. The service sector is being privatized in a country with a population of 140.76 crore.